Perancangan Pengendali Rumah menggunakan Smartphone Android dengan Konektivitas Bluetooth - Angger Dimas Bayu Sadewo; Edita Rosana Widasari; Adharul Muttaqin (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Home is a place to hide and gather with family. The house also has become the basic needs of every person who is married, then have a dream home is everyone's desire. The dream house is a comfortable home to live in. In today's technological developments are very rapidly making the home function in building a dream home to increase the comfort and safety of the inhabitants of the house. In this research will be designed home controller using android smartphone with bluetooth connectivity that can control the home appliance lamp, fan and celenoid door lock with monitoring function and timer padadevice built. In this study can be done in the same way. The result of the functional testing of wireless communications can still be done in the existing space of the wall barrier and the distance of 20 meters in open space. Functional timer goes well according to the added value and how to handle it by the sensor according to the desired result.